Kravchuk’s polynomials and group - Klimik , A. U. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Kravchuk polynomials of a discrete variable and different types of Kravchuk q-polynomials are determined. The importance of these polynomials for the theory of representations of Lie and Chevalley groups and the theory of symmetric and quantum groups is shown. The article presents a survey of the contemporary results in these areas.